Beobachtungen zu Zeitstruktur und Formanlage der mehrthematischen Sätze in Johann Sebastian Bachs ‘Kunst der Fuge’ - Trede, Yngve Jan (Danish Yearbook of Musicology, 1997)
Observations on the time structure and formal layout of the polythematic movements of Johann Sebastian Bach’s ‘Kunst der Fuge’ The article presents the considerations behind the authors attempt to finish the incomplete (quadruple) fugue BWV 1080, 19 from Die Kunst der Fuge (See appendix of article). By analysing primarily the polythematic movements of Die Kunst der Fuge, the author tries to create a basis upon which assumptions concerning the intended overall form of the fragment may be built. Among the aspects focused on are the significance of a movements midpoint as main axis or (in certain cases) as the axis of symmetry, and a possible significance of the Golden Section (represented by the integers of the Fibonacci series) for the relative proportions of the formal sections. Having considered the questions of time structure, key sequence, and the necessity of a separate exposition of the main theme, the author concludes that the barline between bars 192 and 193 (just before the entry of the BACH-theme) constitutes the central axis of the quadruple fugue.